A 22 year review of strategic alliance research in the leading management journals. Issue 1 (February 2016) - Gomes, Emanuel; Barnes, Bradley R.; Mahmood, Tehmina
Highlights: We analyse the contribution of leading management journals to the alliance literature. There has been an upward trend in the number of articles over time. Most articles are empirical in nature and the number of statistical studies has risen sharply. Methodologically, there has been an improvement due to several factors. Interest on topics covering the human side of alliances has been increasing recently. Abstract: This study contributes to the strategic alliance literature by providing a comprehensive review of over 800 articles that have appeared in 22 leading management journals over a 22 year period. Our study reveals that (a) there has been an upward trend to publish articles on this subject over time; (b) a large proportion of these articles are empirical in nature, with a growing number of them reporting on statistical studies that consider variable association and causality; (c) in terms of their methodological rigour we have witnessed relatively larger sized samples, higher response rates and more frequent use of probability sampling; and (d) although the majority of articles were written by authors within the same country and these tended to report on alliances involving North American businesses, we find that a variety of thematic areas have emerged, with cross cultural management and other human related facets receiving greater attention in recent times. Finally, we highlight the study's limitations and based on our review, outline several avenues where future research could be undertaken.